First pregnancy in Latin America using the Piezo-ICSI technique. Case report - Peña, Fernando (2019)
Intracytoplasmic sperm injection (ICSI) is an in vitro fertilization technique in which a sperm is injected through a micropipette to achieve fertilization. This technique, widely used in assisted reproduction, causes a moderate deformation of the oocyte membrane, which becomes harmful in some cases. The Piezo-ICSI technique minimizes this deformation because the Piezo device generates submicron vibration in the ICSI micropipette that crosses the zona pellucida without generating any resistance. There is no prior evidence of a pregnancy obtained through this technique in Latin America. Therefore, we present this report as the first case of a 16-week clinical pregnancy with present heartbeat from an embryo fertilized using the Piezo-ICSI technique.